Penyuluhan dan Aksi Konservasi Lingkungan melalui Penanaman Pohon dan Pemanfaatan Pupuk Organik di Sekolah - Anam, Khoirul; Ikka, Ni Dewi Ambal; Purwanti, Sri; Alam, Mega Citra; Novita, Mega D; Soesanto, Soesanto; Utomo, Budi; Kusumawati, Nur Farida; Aditya, Dipa; Mustaan, Arbikhan (Pakis Journal Institute, 2025)
Low environmental awareness in schools, particularly in the utilization of vacant land, organic waste management, and the need for greening, is the background for this community service program. The objective of the activity is to increase the awareness and skills of school members in environmental conservation. This community service program was implemented as part of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) at SMP and SMAS Karya Gedeg, Ngares Village, Mojokerto Regency. The methods used included field reviews, socialization, practical demonstrations of tree planting and organic fertilizer production (solid and liquid compost), student mentoring, as well as monitoring and evaluation. As an integral part of the program, a School Waste Bank was also established to manage inorganic waste and introduce the circular economy to students. The results of the activities showed high enthusiasm from the participants. Some of the tangible achievements included the planting of trees in the school area, the successful demonstration of organic fertilizer production, and the operation of a waste bank managed by the Student Council. The impacts included increased environmental awareness, skills in processing organic waste, the creation of green spaces, and a culture of waste sorting among students. In conclusion, this program has successfully fostered awareness among the younger generation and provided practical skills in preserving the ecosystem. For sustainability, it is recommended that schools continue the program consistently, students apply their knowledge at home, and local governments provide support. This activity has the potential to become a model for school-based environmental management that can be replicated in other regions.